Automatic simulation calibration: An evaluation of search-based metaheuristics applied to IEC 61131-3 based automation in the power systems domain - Cláudio Silva (2014)
Industrial automation relies on PLC's to perform real-time critical tasks. These tasks are commonly implemented using IEC 61131-3 and tend to be very complex due to the current evolution of microprocessor capabilities. This complexity causes testing to be considered a very difficult task and the scope to be reduced to minimize effort. The application of automatic calibration techniques could allow the identification of optimal or near optimal solutions for the set of inputs to allow a better test coverage and simulation accuracy. This paper reviews current automatic simulation calibration methodologies and provides a description of an experiment of the application of search-based metaheuristics to IEC 61131-3 implemented algorithms in the context of power systems automation.